Extended Breastfeeding in Poland: Knowledge of Health Care Providers and Attitudes on Breastfeeding Beyond Infancy. (May 2019) - Baranowska, Barbara; Malinowska, Marta; Stanaszek, Ewelina; Sys, Dorota; Bączek, Grażyna; Doroszewska, Antonina; Tataj-Puzyna, Urszula; Rabijewski, Michał
Background: Extended breastfeeding is rare in Poland, and lack of acceptance and understanding is often evident in public opinion. The ability to provide reliable information about breastfeeding beyond infancy depends on health professionals' levels of knowledge and attitudes. They are considered by most parents in Poland to be authorities in the field of child nutrition. Research aims: To determine (1) the level of knowledge and the attitudes of Polish health professionals towards extended breastfeeding; (2) the relationship between personal breastfeeding experience and attitudes towards extended breastfeeding; and (3) the relationship between knowledge about breastfeeding beyond twelve months and attitudes towards breastfeeding beyond infancy. Methods: A one-group prospective, cross-sectional, self-report style survey was used. The convenience sample ( N = 495) comprised gynaecologists, neonatologists and midwives. Data were collected via an online questionnaire and the results were analyzed with the use of descriptive statistics, a chi-square independence test, Fisher's exact test, post-hoc testing, and two-part tables using SPSS. Results: Most of the respondents (76.7%; n = 384) had a low level of knowledge about the benefits of breastfeeding beyond twelve months and even emphasized that this nutritional choice could have negative impacts. There was a positive correlation ( F = 105.847; p = < .01) between levels of knowledge and respondents' attitudes towards breastfeeding beyond infancy. Attitudes were also influenced by the length of time respondents had breastfed. Conclusion: Healthcare providers have an insufficient level of knowledge about extended breastfeeding and need further education in this area.